Photoluminescent behavior of BaWO4 powders processed in microwave-hydrothermal - Cavalcante, L. S.; Sczancoski, J. C.; Espinosa, J. W. M.; Varela, José Arana [UNESP]; Pizani, P. S.; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2009)
Photoluminescence (PL) at room temperature was observed in BaWO4 powders processed in microwave-hydrothermal at 140 degrees C for different times. The phases were characterized by X-ray diffraction (XRD) and Fourier transform Raman (FT-Raman) measurements. XRD and FT-Raman analyses revealed that the BaWO4 powders present a tetragonal structure and free of deleterious phases. Ultraviolet-visible absorption spectroscopy was employed to determine the optical band gap of this material. PL measurements at room temperature showed a maximum emission at around 543 nm (green emission) when excited with 488 nm wavelength. PL behavior was attributed to the existence of distortions on the [WO4] tetrahedron groups caused by microwave radiation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Optical materials; Precipitation; Crystal structure; Optical properties; Luminescence